STRESS OF THE INNOVATION AND INNOVATIONS IN EDUCATION - Kassymova G. K.; Valeeva G. V.; Stepanova O. P.; Goroshchenova O. А.; Gasanova R. R.; Kulakova A. A.; Menshikov P. V; Arpentieva M. R.; Dossayeva S. K; Garbuzva G. V. (Scientific Journal of Pedagogy and Economics, 2019)
The authors introduce the concept of stressof the innovation. The stress of innovation is the stress that occurs in the process and result of the introduction of innovation.For students and teachers, innovation is both a situation that generates stresses and crises of the personal, interpersonal and organizational levels, and a way to overcome such stresses, problems, and development crises. It is important to note the relationship of causes and consequences, as well as the manifestations of stress of teachers and students at the personal, interactive, educational and organizational levels.The main objectives of our study are to find out how stress of the innovation in education affects the professional and academic success of teachers and students,and how it’s affect their satisfaction with themselves their health and life in whole. The main method of our research was a theoretical analyze of the problems of stressof innovations by students and teachers. The results obtained show that pupils (students) and teachers need not only training in productive and effective methods of preventing and correcting stress of theinnovationsin situations of organizational and didactic development and stagnation,reforms and other changes. Crisis and stress states of the psyche of a child and an adult are conditions in which the risk of formation and consolidation of deviant behavior, developmental disorders, diseases and injuries, etc. increases. These changes become more pronounced in those cases when, under the conditions of training and education, work and rest, existing and changing relations in the process of innovation and other changes are not taken into account. All productive and effective innovations on education are connected by one idea - creating conditions in which the development of a person as an individual, partner and professional is inevitable, and not just declared or possible.In developing an integrative prevention and coping model for students and teachers (in matetogeniases and pediogeniases), it is important to consider the prevention and correction of stress in the context of the development of the actors of education in different contexts: in the context of educational, professional, personal and interactional development. Prevention and correction of stress in innovative education (and in stress of the innovation) is associated with the prevention and correction of pediogenias (harm caused by incorrect, destructive, and pathologizing attitudes of teachers towards students), as well as correction and prevention of “matetogenias” (harm caused by incorrect, devastating, and pathologizing attitudes of students towards teachers).